1968
DOI: 10.1037/h0026116
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions and patterns of adolescent antisocial behavior.

Abstract: A self-report checklist of antisocial activities was rilled out anonymously by SOS high school boys and 391 boys at institutions for delinquents. The 52 items of the checklist asked the boys about the extent of their participation in a broad range of misbehaviors. Cluster analysis of the items of the scale on 3 different samples revealed 4 dimensions of antisocial behavior: delinquent role, drug usage, parental defiance, and assaultiveness. On each of the 4 dimensions of antisocial behavior, the scores of deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1975
1975
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…This type of scale is still used in the contemporary literature. Second, with the advent of computers, some researchers started to use cluster (Kulik et al, 1968) and factor analysis (Quay and Blumen, 1963), to derive scales representing forms of deviance. This literature has been reviewed by Hindelang et al (1981) for self-reported delinquency and by Cohen (1986) for official delinquency.…”
Section: Deviance Whole or Partsmentioning
confidence: 99%
“…This type of scale is still used in the contemporary literature. Second, with the advent of computers, some researchers started to use cluster (Kulik et al, 1968) and factor analysis (Quay and Blumen, 1963), to derive scales representing forms of deviance. This literature has been reviewed by Hindelang et al (1981) for self-reported delinquency and by Cohen (1986) for official delinquency.…”
Section: Deviance Whole or Partsmentioning
confidence: 99%
“…Forty-eight subjects reported police contact of this nature, for example, trespassing, swearing in public, or throwing eggs at automobiles. Comparison of the mean SRED scores of subjects with and without police contact, as defined by the three sources of information, is shown in Although exploratory factor analysis (Senna, Rathus and Seigal, 1974) and cluster analysis (Hindelang and Weis, 1972;Kulik, Stein and Sarbin, 1968) techniques have been used to develop subscales, results are often less than interpretable (see Hindelang et al, 1981, for review Subscale item clusters approximating dimensions of aggression/assaultiveness, property crime/theft, and drug/alcohol offences. For this study, items were grouped a priori according to face content as theft, interpersonal/aggressive, drug/alcohol, destruction/vandalism.…”
Section: Validitymentioning
confidence: 99%
“…More serious attempts to investigate the structure of their items have been made by several authors who have used parametric statistical procedures, such as cluster analysis (Hindelang, 1971a(Hindelang, , 1971bKulik, Stein, & Sabin, 1968) and principal component analysis (Arnold, 1965;Dembo, 1973; Gibson, 1971;Heise, 1968;Short et al, 1963;Walberg et al, 1974). However, the value of these analyses is also questionable, since self-report delinquency data grossly abuses the metric and distributional assumptions of these parametric techniques.…”
Section: The Scaling Of Delinquencymentioning
confidence: 99%